2000
DOI: 10.1007/s11663-000-0064-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the fundamentals of the kinetics of steelmaking reactions

Abstract: was the leader in developing our understanding of the kinetics of metallurgical reactions. Selected recent kinetic studies, based on this understanding and the application of the results to actual processes, are presented in this article. In particular, the rates of reaction of carbon and carbon in iron with CO 2 and H 2 O gases and FeO in slag are reviewed and applied to the iron smelting process. In addition, our basic understanding of the kinetics of the nitrogen reaction with iron is reviewed, and the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Initial calculation of expected droplet trajectories showed less than a second of existence in the emulsion. [65] However, development of theories around gas generation due to decarburization causing droplet halos or bloating has been key to understanding the relative density of the metal being reduced, and the droplets not only float in the slag layer for an extended period [31,47,51,54,[66][67][68][69] (of up to around 2 minutes depending on size and reaction potential) but also grow slightly to increase interfacial area even more. In addition, the present authors have explored droplet reactions under non-gas-producing conditions and have observed the phenomenon of spontaneous emulsification.…”
Section: Behavior Of Metal Droplets In the Bofmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial calculation of expected droplet trajectories showed less than a second of existence in the emulsion. [65] However, development of theories around gas generation due to decarburization causing droplet halos or bloating has been key to understanding the relative density of the metal being reduced, and the droplets not only float in the slag layer for an extended period [31,47,51,54,[66][67][68][69] (of up to around 2 minutes depending on size and reaction potential) but also grow slightly to increase interfacial area even more. In addition, the present authors have explored droplet reactions under non-gas-producing conditions and have observed the phenomenon of spontaneous emulsification.…”
Section: Behavior Of Metal Droplets In the Bofmentioning
confidence: 99%
“…Two prominent laboratories in the field of pyrometallurgy have produced a series of well-respected journal publications in this immediate area. [49,69,76] They use an experimental setup where a vertical tube furnace is positioned between X-ray radiography equipment. These studies have been invaluable in their findings of gas phase phenomena such as the generation of a ''gas halo'' and ''bloated droplets'' during the decarburization reaction.…”
Section: Gas Phase Production Effects On Free Steel Dropletsmentioning
confidence: 99%
“…[19][20][21][22] Up to 90% of surface coverage may occur with very low levels of sulphur (∼5 ppm). 23 This is known as the surface blockage mechanism, which is responsible for significantly decreasing the rate of carbon transfer from carbon-containing gases into liquid iron. Sulphur is also known for considerably lowering the rate of carbon diffusion in both liquid and solid iron.…”
Section: Further Experimental Aspects Of the Fe-c-s Systemmentioning
confidence: 99%
“…In the presence of sulphur, the solubility of carbon in liquid iron decreases and thus, the carbon atoms tend to combine to each other forming graphite flakes (cast irons) or other carbon-rich phases such as iron carbides (steels). [18][19][20][21][22][23][24][25][26][27][28] Other relevant literature from ferrous metallurgy concerns the formation of so-called grey cast irons. These irons contain particles of graphite precipitated from the melt on cooling the carbon rich melt.…”
Section: Further Experimental Aspects Of the Fe-c-s Systemmentioning
confidence: 99%
“…In the case of solid carbon reacting with slag, Fruehan et al [18] suggested for higher FeO contents, a mixed control regime involving the slag/gas reaction, transport in the halo and gas/carbon reaction. Story et al [19] suggested that for graphite the rate was typically controlled by the gas/slag reaction and mass transport in the slag.…”
Section: Reduction Of Oxides In Slag By Carbonmentioning
confidence: 99%